Pendampingan Manajemen Sumber Daya Manusia Sederhana pada Pelaku UMKM Gerakan Pemuda Ansor di Pagedangan Tangerang - Rahmi Hermawati; N Lilis Suryani; Fitri Sabina (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This community service activity was conducted to address the limited understanding of simple human resource management among Micro, Small, and Medium Enterprises (MSMEs) members of Gerakan Pemuda Ansor in Pagedangan, Tangerang. The aim of this PKM program is to provide assistance and training in simple human resource management to improve organizational capacity and business management skills. Methods of implementation were carried out at Balai Desa Cicalengka, Pagedangan District, Tangerang Regency on May 19, 2026, involving three lecturers from Universitas Pamulang and 32 participants from Gerakan Pemuda Ansor. Activities were conducted through material presentations, practical exercises, group discussions, and question and answer sessions. The implementation stages included preparation, execution, and reporting phases to ensure systematic and structured community service delivery. The results of the program showed increased understanding of simple human resource management among participants and improved awareness of organizational management practices in MSMEs. Participants were able to apply basic HR management concepts to support the development of their MSME activities effectively. Overall, this program contributed positively to strengthening human resource practices within the community-based MSME environment in Pagedangan. It is expected that continuous mentoring will sustain better organizational performance and encourage more structured management among MSME actors in the future.